The Adolescent and Young Adult (AYA) Horizon Study: An AYA cancer survivorship cohort - Nichols, Hazel B. (Cancer Epidemiol Biomarkers Prev, 2021)
BACKGROUND: In the United States (U.S.), >45,000 adolescent and young adult (AYA) women are diagnosed with cancer annually. Reproductive issues are critically important to AYA cancer survivors, but insufficient information is available to address their concerns. The AYA Horizon Study was initiated to contribute high-quality, contemporary evidence on reproductive outcomes for female cancer survivors in the U.S. METHODS: The study cohort includes women diagnosed with lymphoma, breast, melanoma, thyroid, or gynecologic cancer (the 5 most common cancers among women ages 15–39 years) at three study sites: the state of North Carolina and the Kaiser Permanente health systems in Northern and Southern California. Detailed information on cancer treatment, fertility procedures, and pregnancy (e.g. miscarriage, livebirth) and birth (e.g. birth weight, gestational length) outcomes are leveraged from state cancer registries, health system databases and administrative insurance claims, national data on assisted reproductive technology procedures, vital records, and survey data. RESULTS: We identified a cohort of 11,072 female AYA cancer survivors that includes >1,200 African American women, >1,400 Asian women, >1,600 Medicaid enrollees, and >2,500 Hispanic women using existing data sources. Active response to the survey component was low overall (N=1,679), and notably lower among minority groups compared to non-Hispanic white women. CONCLUSIONS: Passive data collection through linkage reduces participant burden and prevents systematic cohort attrition or potential selection biases that can occur with active participation requirements. IMPACT: The AYA Horizon study will inform survivorship planning as fertility and parenthood gain increasing recognition as key aspects of high-quality cancer care.